Pengaruh Motivasi, Kepuasan Kerja dan Disiplin Kerja terhadap Kinerja Karywan pada PT. Bahtera Bahari Shipyard di Kota Batam - Dhiya Ulha Qiyah; Mauli Siagian (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
This study aims to determine empirically about the influence of motivation, job satisfaction and work discipline on the performance of the employees of PT Bahtera Bahari Shipyard. A sample of 155 respondents. The instrument used to collect data was a questionnaire. The sampling technique used is Random Sampling where sampling provides equal opportunities for each element or member of the population to be selected as a sample. Test data in this study are validity, reliability, classic assumptions, multiple linear analysis of the coefficient of determination (R2), t-test and f test. The data were processed using SPSS version 25. The results of the study found t count> t table is 4.807> 1.976 and significant value of 0.000 <0.05. This means that motivation has a positive and significant effect on the performance of employees of PT Bahtera Bahari Shipyard. t calculate the known job satisfaction> t table is 2.290> 1.976 and a significant value of 0.000 <0.05. This means that job satisfaction has a positive and significant effect on the performance of the employees of PT Bahtera Bahari Shipyard. t calculate known work discipline> t table is 4.174> 1.976 and a significant value of 0.000 <0.05. This means that the work discipline has a positive and significant effect on the performance of the employees of PT Bahtera Bahari Shipyard. And there is motivation, job satisfaction, and employee discipline together have a positive and significant effect on employee performance. Evidenced by the results of the F test (simultaneous) F value of 27,197 (Fcount)> 3.05 (Ftable). And the value is significant at 0,000 <0.05.